ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG DAGANG SEBAGAI EVALUASI PENGENDALIAN INTENAL PADA PT EPSON BATAM - Puspita Rama Nopiana (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
Problems that always in PT Epson Batam in maintaining the quality of goods, must pay attention to the occurrence the risk of accidentally losing goods caused. The purpose of this study is how the application of inventory information accounting systems and evaluation of internal control of PT Epson’s inventory. Survey research method which is a study that takes samples from a population and uses questionnaires as a basic data collection tool. The population of this study is employees or employees of parts of PT. Epson Batam as many as 30 people, so the sample of this study is saturated samples, so that all population numbers are used as research samples. The results of the study explained that: 1) the application of merchandise inventory accounting information systems can be seen from the elements studied having an assessment of 83.33% (good), so that activities that support the accounting information system can be carried out in accordance with existing procedures, 2 ) Evaluation of Intellectual Control in merchandise inventory can be assessed from the elements studied in general the average value for the internal control variable of merchandise inventory is 82.73% which has good assessment criteria. This shows that the supply of merchandise can be safeguarded, checks the accuracy and correctness of accounting information, increases the operational efficiency of the company and helps maintain established management policies